Halloween 2 - Carpenter, John.; Curtis, Nancy; Kyes PJ Soles; Brian Andrews; Charles Cyphers; Jamie Lee; Kyle Richards; Donald Pleasence (USA Compass International Pictures, 1978)
Michael Myers has been in an institution since he was a young boy, after murdering his sister. Now he's escaped and is heading back home to terrorise the quiet community which still remembers him.
A psychotic murderer institutionalized since childhood escapes on a mindless rampage while his doctor chases him through the streets.
John Carpenter
Language(s): English, Turkish
Subtitle(s): Turkish
Keywords: Thriller; Horror